Metaverse in the Play; A Strategy for Early Childhood Educators - Habibat Bolanle ABDULKAREEM; Akeem Omowunmi RAHEEM; Jamiu Babatunde Bello,; Shamsudeen Shola IBRAHIM; Rukayat Adetoun ABDULKAREEM (Universitas Pendidikan Ganesha, 2025)
Early childhood education (ECE) plays a vital role in supporting children’s holistic development, yet traditional teaching methods often fail to meet diverse learning needs in today’s digital era. The main challenge lies in effectively integrating technology to enhance children’s engagement, creativity, and social interaction. This study explores the potential of the Metaverse as an innovative platform for early childhood education, examining how immersive, interactive virtual environments can enhance cognitive, social, and emotional development. Specifically, the research adopted a qualitative exploratory design involving 20 early childhood educators drawn from selected nursery schools. Data were collected through semi-structured interviews and focus group discussions, and were analysed thematically to generate insights into educators’ perceptions and experiences. Findings reveal that Metaverse platforms can support diverse learning styles, facilitate playful and collaborative teaching methods, and provide opportunities for personalized learning that go beyond the limits of traditional classrooms. The study concludes that Metaverse technology offers transformative possibilities for enhancing teaching and learning in early childhood education. The implications suggest that policymakers, curriculum developers, and educators should consider strategic adoption of Metaverse tools, while further research is needed to optimize their integration and address ethical and developmental concerns.